Parasitic insect-derived miRNAs modulate host development - Zhi-zhi Wang (Nature Portfolio, 2018)
The moth Plutella xylostella during its larval stage is the host of the endoparasitic wasp Cotesia vestalis. Here the authors show that the parasitoids deliver microRNAs to their hosts through their symbiotic virus and specialized cells leading to induced developmental delay.